The Role of Islamic Education Teachers in Instilling Religious Moderation Attitudes in Junior High School Students Throughout Idi Rayeuk - Masyithah Masyithah; Ismail Fahmi Arrauf Nasution; Mulyadi Mulyadi (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study investigates the role of Islamic Religious Education teachers in influencing religious moderation attitudes among junior high school pupils in Idi Rayeuk, the problems they face, and the tactics utilized to impart these values. A qualitative research methodology was employed, utilizing data gathered through interviews, observations, and documentation. There were three steps in the data analysis: reducing the data, showing the data, and making conclusions. The findings indicate that IRE teachers serve a strategic function in promoting religious moderation through three primary roles: as educators who nurture tolerance and mutual respect, as role models who exemplify equitable, transparent, and balanced perspectives, and as guides who stress the importance of steering clear of extreme religious conduct. But teachers have a lot of problems to deal with, like the tremendous influence of social media that has intolerant material, conservative social surroundings, students' low digital literacy, and community figures who may support narrow-minded views. To deal with these problems, IRE teachers use systematic methods by making sure that moderation ideals are present in all learning materials and by using personal approaches with students who show intolerant behavior. These tactics help students not only grasp religious moderation on a cognitive level, but also generate positive feelings and behaviors in their daily lives.